Respuesta :
[tex]{x}^{2} + 3 x - 10 = 0 \\ (x + 5)(x - 2) = 0 \\ x + 5 = 0 \: (or) \: \: x - 2 = 0 \\ \: x = - 5 \: \: \: \: (or) \: \: \: \: \: \: \: \: x = 2[/tex]
for better understanding in the first step please see factoring quadratic equation in khan academy
Hey there!!
We have:
... x²+3x-10=0
Now, let's split the middle term. We will have to split the middle term in a way that the terms we got have common in x³ and -10.
... x²+3x-10=0
We will have to split 3x with the help of factor of -10.
... -10 = 5×(-2)
Hence, we can write the equation as:
... x² - 2x + 5x - 10 = 0
Taking common terms:
... x(x-2)-5(x-2)=0
... (x+5)(x-2)=0
Now, we have 2 equations
... x+5=0 and x-2=0
... x+5=0
... x=-5
... x-2=0
... x=2
Hence, the two answers of this equation are -5 and 2.
Hope my answer helps!